Research and Implementation of Hungarian Method Based on the Structure Index Reduction for DAE Systems. Issue 2 (June 2014) - Zeng, Yan; Wu, Xuesong; Cao, Jianwen
Hungarian method is a classical method for solving assignment problems. It also can be widely used in other problems, such as matching problem. This paper researches its application on using structural index reduction method to solve high-index DAEs, based on the combinatorial relaxation theory. Combinatorial relaxation theory converts the complex mathematical problem to the matching problem of bipartite graph. Based on this theory this paper presents the main idea of Hungarian method and puts up three implementations for Hungarian method. At last, it compares the time performance of the three implementations by running a set of experiments.